Negative Effects of Hate Crime on Athletes - Dobson, Micah J. (European Journal of Applied Sciences, 2025)
Hate crimes continue to be a problem in many industries, including the realm of athletics. The crimes that stem from a prejudicial attitude toward a person’s features lead to discrimination, physical violence, and psychological suffering for the victim. This article review assesses the consequences of hate crimes on athletes, particularly those with diverse sexual orientations and dispositions. Following the current trends in criminological studies and sports science on the one hand and taking into consideration the problems that minority athletes face on the other hand, this review will attempt to address and emphasize issues that create a safe and discrimination-free environment for the activities of minorities. The term hate crime is used to describe different unlawful acts that are performed as a result of prejudice that is directed to specific characteristics such as race, homosexual and lesbian characteristics, gender, or physical disability. It is in sports that athletes from minority communities become the victims of such crimes, and they pay a hefty price through the physical, psychological, social, and economic ramifications. This article review aims to review qualitative and quantitative research that reveals the interests of these athletes and ensures a comprehensive understanding of the ramifications of hate crimes.